Predictive Value of Triglyceride-Glucose Index for In-hospital Mortality in Patients With Severe Fever With Thrombocytopenia Syndrome: A Multi-Center Observational Study - Zhang, Tingyu; Liu, Yuanni; Ge, Ziruo; Tian, Di; Lin, Ling; Zhao, Zhenghua; Shen, Yi; Yu, Xiaoli; Feng, Yang; Qiang, Chunqian; Duan, Jianping; Ma, Yanli; et al. (Frontiers in Medicine, 2022)
Background: Triglyceride-glucose (TyG) index has been proposed as a reliable indicator for insulin resistance and proved to be closely associated with the severity and mortality risk of infectious diseases. It remains indistinct whether TyG index performs an important role in predicting in-hospital mortality in patients with severe fever with thrombocytopenia syndrome (SFTS). Methods: The current study retrospectively recruited patients who were admitted for SFTS from January to December 2019 at five medical centers. TyG index was calculated in accordance with the description of previous study: Ln [fasting triglyceride (TG) (mg/dL) × fasting blood glucose (FBG) (mg/dL) / 2]. The observational endpoint of the present study was defined as the in-hospital death. Results: 79 patients (64.9±10.5 years, 39.2% female) who met the enrollment criteria were ultimately enrolled in the current study. During the hospitalization period, 17 (21.5%) patients died in hospital. TyG index remained a significant and independent predictor for in-hospital death despite fully adjusted for confounders, either being taken as a nominal [hazard ratio (HR) 5.923, 95% confidence interval (CI) 1.208-29.036, P=0.028] or continuous (HR 7.309, 95% CI 1.854-28.818, P=0.004) variate. TyG index exhibited a moderate-to-high strength in predicting in-hospital death, with an area under the receiver operating characteristic curve (AUC) of 0.821 (95% CI 0.712-0.929, P<0.001). The addition of TyG index displayed significant enhancement on the predictive value for in-hospital death beyond a baseline model, manifested as increased AUC (baseline model: 0.788, 95% CI 0.676-0.901 vs. + TyG index 0.866, 95% CI 0.783-0.950, P for comparison=0.041), increased Harrell’s C-index (baseline model: 0.762, 95% CI 0.645-0.880 vs. + TyG index 0.813, 95% CI 0.724-0.903, P for comparison=0.035), significant continuous net reclassification improvement (0.310, 95% CI 0.092-0.714, P=0.013), and significant integrated discrimination improvement (0.111, 95% CI 0.008-0.254, P=0.040). Conclusion: TyG index, a novel indicator simply calculated from fasting TG and FBG, is strongly and independently associated with the risk of in-hospital death in patients with SFTS.